Construction shaft of the Koralm Tunnel lot KAT 2 – a challenge in structural analysis, geotechnics and logistics / Der Bauschacht des Koralmtunnels Baulos KAT 2 – eine statische, geotechnische und logistische Herausforderung. Issue 5 (1st October 2013) - Moritz, Bernd; Radoncic, Nedim; Helmberger, Albert; Uschan, Robert
Abstract The paper deals with the challenge on structural analysis, logistics as well as on geotechnical aspects during sinking of an approximately 60 m deep construction shaft with a cross‐sectional area of about 720 m2 at the Koralm Tunnel lot KAT 2. Numerical 3D simulations were used for the structural analysis. The results in terms of level of loading of the support measures and the displacements served as a basis for predicting the system behaviour of the shaft. During sinking, the behaviour of the shaft and surface was continuously monitored within the geotechnical safety management by means of 3D displacement measurements, measurement of strains in the shotcrete lining and measurements of pile inclinometers. Thereby a continuous target‐performance comparison was accomplished. Special characteristics in the design and construction phase are illustrated and discussed. Der Beitrag behandelt die Herausforderung an die statische Berechnung, die Logistik im Zuge des Abteufens sowie an die Geotechnik beim rund 60 m tiefen Bauschacht des Koralmtunnels Baulos KAT 2 mit einer Querschnittsfläche von insgesamt ca. 720 m2. Die statische Berechnung erfolgte mittels numerischer 3D‐Simulationen. Die Ergebnisse in Bezug auf Auslastungsgrad der Stützmittel und Verschiebungsausmaß dienten in weiterer Folge als Basis für die Prognose des Systemverhaltens des Schachtbauwerks. Im Zuge des Abteufvorgangs erfolgte im Rahmen des Geotechnischen Sicherheitsmanagements eine lückenlose Überwachung des Schachtbauwerks über 3D‐Verschiebungsmessungen an der Oberfläche und der Schachtlaibung, Messung von Dehnungen in der Spritzbetonaußenschale sowie über Bohrpfahlinklinometer. Dabei wurde ein ständiger Soll‐Ist‐Vergleich geführt. Besonderheiten in der Planung und Bauausführung werden aufgezeigt und diskutiert.